Intervenciones de enfermería para la prevención del cáncer de piel - Velasco Paredes, Nancy Yesenia (2025)
Background: One of the potential pathologies of cancer, are cells in the body that grow uncontrollably. The most frequent symptoms are lesions that do not heal, or changes of moles that manifest in areas that are exposed to the sun, such as the scalp, face, neck, arms, hands; its diagnosis needs to be made with a physical examination and biopsy whose treatment will depend on early and timely detection, followed by the removal of the carcinoma. Objective: To know the nursing interventions for the prevention of skin cancer through a systematic review of the literature. Methods: The research has a qualitative approach, based on the systematic - narrative type of literature review study. In addition, it was documented with indexed studies and journals conducted in the last 5 years. The exclusion criteria included incomplete documents and works in non - prestigious platforms. Results: Nursing interventions are scientifically established for the prevention of skin cancer such as education, postoperative care, management as in chemotherapy treatments, radiotherapy, palliative care and emotional support, for the application in the nursing care process and thus contribute to improve the quality of life of the patient, which will contribute positively. Conclusions: The intervention of the nurse plays an important role in prevention, delaying the different types of neoplasms, such as premature recognition of this pathology to be able to be controlled in an adequate manner, encouraging promotion and prevention.